Enhancement of Heat Transfer Coefficient in an Automobile Radiator Using Multi Walled Carbon Nano Tubes (MWCNTS) - Ramaraju, Ramgopal Varma; Manikantan, Kota; Vasudeva , Rao Veeredhi; Hadi, Manap (2014)
Enhancement of heat transfer coefficient continues to be an important research area in various fields of engineering ranging from microelectronics to high powered automobiles. The initial effort in the present research study is to enhance the heat transfer coefficient in a vehicle radiator using nanofluids with high thermal conductivity. The world’s most abundant element ‘Carbon’ astoundingly exists in various structures and one such form is tube commonly known as Carbon Nanotubes (CNTs). Heat transfer enhancement in water and coolant based systems with different concentrations of nano particles (carbon nanotubes) have been investigated from an engineering system perspective. One such system considered is a “SUZUKI (800CC) - CAR RADIATOR”, cooling circuit using different nanofluids to replace the conventional engine coolant. In the present study, the effect of nano-fluid heat transfer to enhance in water and coolant based systems with multi walled carbon nanotubes has been investigated. The improvement of heat transfer when compared to water, coolant (water + ethylene glycol 60:40) and water with MWCNTS and coolant with MWCNTS has been studied. It has been observed that there is an enhancement of heat transfer up to 30% when coolant and CNTS are used as a cooling medium.